Blending of technology and modern day medical biomedical devices: an overview - MS .KEERTHANYA RAJESH, (International Journal of Pharma and Bio Sciences, 2016)
Advances in health care reached a pinnacle in a new dimension in the last decade. Blended technology with medicine has escalated the scope of their applications in medical care. Apart from widely heard and discussed robotic surgery, there are many recent computers assisted or sensing devices which are used in day to day life of many patients. They intend to treat chronic diseases and thereby improve quality of life and also useful in many emergency condition. This forum tends to provide a comprehensive coverage of very recent and significant biomedical devices and their unique feature.